PERSEPSI PELAKU UMKM INDUSTRI FURNITURE DALAM MENINGKATKAN DAYA SAING USAHA DI ERA DIGITAL (Studi Kasus Pada Pelaku UMKM di Kota Tangerang Selatan) - Effendy, Aidil Amin; Sunarsi, Denok; Seta, Anggada Bayu; Mulyani, Sri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to explore the perceptions of small and medium-sized enterprises (SMEs) in the furniture industry regarding enhancing business competitiveness in the digital era (a case study of SMEs in South Tangerang City). This research employs a qualitative method to gain in-depth understanding through data collection techniques including observation, documentation, and interviews, using a semi-structured interview format based on a predetermined interview guide with several informants from the furniture industry SMEs in South Tangerang City. The analysis of the interviews revealed that the strategies employed to improve competitiveness in the digital era focus on maintaining product quality, utilizing social media and e-commerce, and building good relationships with customers. Although some business actors have started using digital platforms, many still rely on traditional methods. Challenges such as price competition and the impact of political situations are also faced, but these are addressed through innovation, product differentiation, and strategic adaptation. While there have been efforts to leverage digital opportunities, there remains room for further development in the use of technology and more effective online marketing strategies.